ANALISIS SEBARAN MAKAM ADAT TORAJA DI KECAMATAN SESEAN SULOARA KABUPATEN TORAJA UTARA - Elisabet Tampang; Xaverius Erick Lobja; Denny Maliangkay (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
The problem in this research is that there is not yet a map of the distribution of customary tombs in Sesean Suloara District, North Toraja Regency. The results of the study explain that there are geographical and cultural problems that play a big role in determining the location of customary cemeteries. The research aims to describe the factors that influence the distribution of Toraja customary tomb patterns in Sesean Suloara District, North Toraja Regency. The process of descriptive qualitative research method with spatial approach (space) aims to analyze the distribution pattern of customary tombs in Sesean District Suloara North Toraja Regency. Analysis data is sourced from field surveys, interviews, observations and using GIS applications. The results of the parameter analysis of the distribution pattern of Sesean Suloara Subdistrict, North Toraja Regency, the nearest neighbor are 1.66 by paying attention to the continuity of the value of the analysis of the nearest neighbor. The distribution pattern of tombs in Sesean Suloara Subdistrict is an uneven (random pattern), distribution is identified along the Sapan-Pangli road.